Best Practices for Minimizing Rejection and Optimizing Acceptance Among Learners Seeking Online Assistance: A Qualitative Study - Deever, Don; Grubaugh, Steven; Levitt, Greg; Maderick, Joe; Gonzales, Gabe (Eximia, 2022)
Observing an online community of computer programmers from an insider’s perspective, a team of ethnographic researchers were able to carefully monitor the manner in which international newcomers, just getting into the arena of computer programming, were able to successfully, and not-as-successfully, garner assistance from highly experienced programmers. From the qualitative transcripts of the communications between these newcomers and their professional counterparts, it was observed that there seems to exist implied unwritten protocols among software developers and new students of technology, which when followed either knowingly or intuitively, seemed to lead to better quality assistance and more fluent explanations from helpers. This study describes and defines the top ten best practices that were identified and explains the potential significance of emulating those protocols in a wide variety of online communities to assist novices to become more proficient in many academic and non-academic fields.